IFPRI 2012 Global Food Policy Report China Launch (in Chinese) - Fan, Shenggen (2013)
Presentation by IFPRI Director General Shenggen Fan at the 2012 Global Food Policy Report China Launch event in Beijing on June 4, 2013.